Mental illness and housing outcomes among a sample of homeless men in an Australian urban centre. (May 2015) - Spicer, Bridget; Smith, David I; Conroy, Elizabeth; Flatau, Paul R; Burns, Lucy
Objective: The over-representation of mental illness among homeless people across the globe is well documented. However, there is a dearth of Australian literature on the mental health needs of homeless individuals. Furthermore, longitudinal research examining the factors that contribute to better housing outcomes among this population is sparse. The aim of this research is to describe the mental illness profile of a sample of homeless men in an Australian urban centre (in Sydney) and examine the factors associated with better housing outcomes at 12-month follow-up. Methods: A longitudinal survey was administered to 253 homeless men who were involved in the Michael Project: a 3-year initiative which combined existing accommodation support services with assertive case management and access to coordinated additional specialist allied health and support services. A total of 107 participants were followed up 12 months later. The survey examined the demographics of the sample and lifetime mental disorder diagnoses, and also included psychological screeners for current substance use and dependence, psychological distress, psychosis, and post-traumatic stress. Results: Consistent with existing literature, the prevalence of mental illness was significantly greater amongst this sample than the general Australian population. However, mental illness presentation was not associated with housing situation at 12-month follow-up. Instead, type of support service at baseline was the best predictor of housing outcome, wherein participants who received short to medium-term accommodation and support were significantly more likely to be housed in stable, long-term housing at the 12-month follow-up than participants who received outreach or emergency accommodation support. Conclusions: This study provides evidence to support an innovative support model for homeless people in Australia and contributes to the limited Australian research on mental illness in this population.